Understanding Deterrence Theory in Security Compliance Behavior: A Quantitative Meta-Analysis Approach - Abed, Javad (2016)
Nowadays, one of the major concerns in assuring information systems security (ISS) is the employees’ non-compliance behavior. Several studies have investigated compliance behavior by utilizing several behavioral theories and models. Deterrence theory is one of the widely used theories in ISS literature in order to investigate compliance behavior. Based on this theory, behaviors can be controlled by the threat of severe, certain and swift sanctions. This study aims to conduct a quantitative meta-analysis of existing literature to investigate relationship between constructs of deterrence theory (severity, certainty and celerity) and compliance behavior of employees. Results show that deterrence theory has not a remarkable impact on employees’ compliance behavior